WOUND HEALING PROPERTIES OF SYMPLOCOS RACEMOSA - Dr. M. Lakshmi Prabha, N. Sreejit, (International Journal of Innovative Research in Medical Science, 2016)
India has a rich variety of flora that is widely distributed throughout the country. Herbal medicines have been the basis of treatment and cure for various diseases and physiological conditions in traditional methods practiced such as Ayurveda, Unani and Siddha. Medicinal components from plants play an important role in traditional as well as western medicine. Plant derived drugs has played an important role in the evolution of human, healthcare for thousands of years. Plant based drugs were commonly used in India and China. Today a substantial number of drugs are developed from plants which are active against a number of diseases. Ayurveda is considered as the oldest medical science of the Indian Subcontinent. It has been practiced since 1000 B.C., with the objective to accomplish physical, mental, social and spiritual wellbeing, by adopting health-promoting and holistic approach towards life (Patwardhan et al., 2005). In today’s contemporary era, main emphasis is given on plant research. This is because of the fact that large evidence has been made available to show the huge potential of medicinal plants in various traditional systems (Bora et al., 2011) Symplocos racemosa or Lodhra is a common indigenous drug, mentioned in Ayurvedic classics as a remedy for various human ailments. In Sanskrit “Lodhra” means „Propitious‟& „Tilaka‟, since the bark of the tree was used in making the Tilaka mark on the forehead (De Silva et al., 1979). Lodhra is even mentioned to as “DIVYA AUSHADHI” (Divine herb). Symplocos racemosa is a critically endangered medicinal plant attaining a height up to 10 m.Bark: Bark is smooth or rough, grey or in young parts yellowish. Leaf: Leaves are simple, alternate, lanceolate-oblong, oblong, elliptic or ellipticlanceolate, margin serrate, crenate, serrulate or entire, apex acute to acuminate or obtuse at both ends, surface glabrous or slightly pilose on the midrib.